2015
DOI: 10.1002/aoc.3269
|View full text |Cite
|
Sign up to set email alerts
|

A versatile method for the synthesis of diaryl and alkyl aryl ketones via palladium‐catalysed cross‐coupling reaction of arylboronic acids with acyl chlorides

Abstract: An efficient catalytic system using 1‐benzyl‐4‐aza‐1‐azoniabicyclo[2.2.2]octane chloride and PdCl2 was developed for the cross‐coupling reaction of arylboronic acids with acyl chlorides. The catalytic amount of this homogeneous catalytic system affords the corresponding diaryl and alkyl aryl ketones in good to excellent yields under mild reaction conditions. Copyright © 2015 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…In 2015, in continuation of their studies on 1-benzyl-4-aza-1-azonia-bicyclo[2.2.2]octane chloride-palladium chloride complex [(BeDABCO) 2 Pd 2 Cl 6 ], Rafiee and co-workers found that this catalyst was highly active for acylative cross-coupling of acyl chlorides with boronic acids (Scheme 2A) [20]. This reaction allowed for the use of various acyl chlorides and arylboronic acids under mild and phosphine-free conditions.…”
Section: Suzuki Cross-coupling Of Acyl Halidesmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2015, in continuation of their studies on 1-benzyl-4-aza-1-azonia-bicyclo[2.2.2]octane chloride-palladium chloride complex [(BeDABCO) 2 Pd 2 Cl 6 ], Rafiee and co-workers found that this catalyst was highly active for acylative cross-coupling of acyl chlorides with boronic acids (Scheme 2A) [20]. This reaction allowed for the use of various acyl chlorides and arylboronic acids under mild and phosphine-free conditions.…”
Section: Suzuki Cross-coupling Of Acyl Halidesmentioning
confidence: 99%
“…Recently, there have been major developments in the acyl Suzuki cross-coupling of aryl esters (Schemes [16][17][18][19][20]. There are several key advantages of using ester electrophiles in the acyl Suzuki cross-coupling, including (i) high-stability, (ii) prevalence in organic synthesis, (iii) opportunities for orthogonal cross-coupling strategies, (iv) reduction of toxic waste produced in the cross-coupling step.…”
Section: Suzuki Cross-coupling Of Estersmentioning
confidence: 99%
“…The conventional method is Friedel-Cras acylation of arenes, which has drawbacks such as the requirement for superstoichiometric amounts of Lewis acid and low regioselectivity. 9,10 Alternative synthetic approaches have been developed, including oxidation of secondary alcohols, 11,12 acylation of organometallic reagents, [13][14][15][16] transition-metal-catalyzed cross-coupling reactions of carboxylic acid derivatives with organometallic reagents, [17][18][19][20][21][22][23][24] palladium-catalyzed carbonylative cross-coupling reactions between aryl halides and related compounds with carbon nucleophiles, [25][26][27][28][29][30] acylation of (hetero)aryl halides with aldehydes, 31 decarboxylative cross-coupling reactions, 32,33 decarboxylative addition reactions, 33 and other uncommon reactions. 34 Unfortunately, there remain a number of limitations with regards to expensive catalysts, safety concerns, and environmentally practical considerations.…”
Section: Introductionmentioning
confidence: 99%
“…Cross‐coupling reaction of aryl boronic acids with carboxylic acid derivatives over palladium catalysts has emerged as a powerful tool for the synthesis of biaryl ketones . Reports by Yamamoto et al .…”
Section: Resultsmentioning
confidence: 99%